Yahoo奇摩 網頁搜尋

  1. ...point, both the first partial derivatives with respect to x and y must be equal to zero. In view of the results above, only the point (0,0,0) can be a stationary point since 0 ≦ x2...

    分類:科學及數學 > 數學 2007年01月12日

  2. 1) Let θ be the angle of the sector. The length of the loop in cm : 13... and AEFG are similar, and thus the corresponding lengths are inequal proportion. BC / EF = AB...

    分類:科學及數學 > 數學 2014年08月25日

  3. Let b be the height of B above XY.b / BP = sin32...sin81.29161° d = 3sin81.29161° = 2.965 cm then the height of C above XY = d + b = 2.965... error : ∠RAP should be ∠BAP.

    分類:科學及數學 > 數學 2012年07月29日

  4. ... by the manufacturer: $ 1200 x ( 1- 15 % ) = $ 1020 Hence $ 1020 will be the cost price of the watch in view of the shopkeeper. Then selling price of the watch offered by...

    分類:科學及數學 > 數學 2007年09月02日

  5. ...just because f1,f2,f3...f8 = f2,f3...f8,f1 = ...=f8,f1...f7) Since the wreath can be viewed from both sides, so the actual number of ways=7!/2 (since f1,f2,f3,f4,f5,f6,f7,f8 can be viewed as equal as...

    分類:科學及數學 > 數學 2011年08月05日

  6. ... the height of the original pyramid = 8√2 cm. (b) Now, the cross-sectional view of the pyramid can be shown as follows: 圖片參考:http://i117.photobucket.com/albums...

    分類:科學及數學 > 數學 2007年03月20日

  7. ... of the hemisphere = (π/12) cm3 So (2/3)πr3 = π/12 → r = 0.5 cm where r is the radius of hemisphere. (b) With reference to the cross-sectional view of the solid below: 圖片參考:http://i117.photobucket.com/albums/o61/billy_hywung...

    分類:科學及數學 > 數學 2007年03月20日

  8. ...8 = 8 / 5 5 + BN = 64 / 5 BN = 39 / 5 = 7.8 2. Let x be the capacity of the small buckets. Then the volumes of flour and suger in bucket...

    分類:科學及數學 > 數學 2007年08月17日

  9. ... the nature of the entity's activities and irrespective of whether cash can be viewed as the product of the entity, as may be the case with a financial institution. Entities need cash for...

    分類:科學及數學 > 數學 2008年04月24日

  10. From the information given, a and b can be viewed as the roots of the quadratic equation x^2 - 4x - 3 = 0 So, a + b = 4, ab = -3 (a + 1)(b + 1) = (a + b) + ab + 1 = 4 - 3 + 1 = 2

    分類:科學及數學 > 數學 2011年09月27日